2014
DOI: 10.3897/zookeys.422.7779
|View full text |Cite
|
Sign up to set email alerts
|

Then there were five: a reexamination of the ant genus Paratrechina (Hymenoptera, Formicidae)

Abstract: The ant genus Paratrechina is reexamined based on the discovery of two new species from Madagascar (P. ankarana sp. n. and P. antsingy sp. n.). Paratrechina kohli, a species known from central Africa, is transferred to Paratrechina from Prenolepis based on a new morphological interpretation of the genus and an updated morphological diagnosis of the genus is provided. This means that other than the widespread P. longicornis, whose origins remain uncertain, all Paratrechina are restricted either to the Afrotropi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 13 publications
0
17
0
Order By: Relevance
“…Unlike the conflicts involving T. allaborans and T. pacificum , Paratrechina longicornis was a case of morphologically identical specimens being sorted into two separate mOTUs differing by 5% (average uncorrected p ‐distances). Bearing in mind that P. longicornis is a widespread cosmopolitan species (Fox et al., ; McGlynn, ) of disputed native range (LaPolla & Fisher, ; Wetterer, ), high genetic variability in Asia may imply multiple introductions or one introduction involving multiple haplotypes (Bergsten et al., ; Wild, ). This species appears morphologically uniform despite high underlying genetic variability in mitochondrial markers.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike the conflicts involving T. allaborans and T. pacificum , Paratrechina longicornis was a case of morphologically identical specimens being sorted into two separate mOTUs differing by 5% (average uncorrected p ‐distances). Bearing in mind that P. longicornis is a widespread cosmopolitan species (Fox et al., ; McGlynn, ) of disputed native range (LaPolla & Fisher, ; Wetterer, ), high genetic variability in Asia may imply multiple introductions or one introduction involving multiple haplotypes (Bergsten et al., ; Wild, ). This species appears morphologically uniform despite high underlying genetic variability in mitochondrial markers.…”
Section: Discussionmentioning
confidence: 99%
“…High heterozygosity of workers, close association with humans, and high adaptability in disturbed environments of this species may help explain to some extent how this ant spread rapidly around the world even prior to the 20 th century (Weber, 1939; Harris and Berry, 2005; Lester, 2005; Wetterer, 2008; Pearcy et al, 2011). While the precise native range of this ant has been a source of debate and remains uncertain, distribution records of P. longicornis and its closest relatives suggest either a Southeast Asian or African origin (Wetterer, 2008; LaPolla et al, 2010; LaPolla et al, 2013; LaPolla and Fisher, 2014). A comprehensive phylogeographic study of P. longicornis is needed to help identify more precisely where the species originated as well as its subsequent dispersal routes around the globe.…”
Section: Introductionmentioning
confidence: 99%
“…The longhorn crazy ant, Paratrechina longicornis (Latreille, 1802), is regarded as a signifi cant invasive species due to its ecological impacts (Wetterer, 2008). The native range of this invasive species and its invasion history, however, remain controversial (Wetterer, 2008;LaPolla & Fisher, 2014). A previous study reported that colonies of P. longicornis from Bangkok, Thailand display a remarkable genetic system, whereby workers are produced by sexual reproduction, whereas queens are clones of their mothers and males are clones of their fathers (Pearcy et al, 2011).…”
Section: Resultsmentioning
confidence: 99%